Multiple groups of endogenous epsilon-like retroviruses conserved across primates - Brown, Katherine; Emes, Richard D.; Tarlinton, Rachael E. (American Society for Microbiology, 2014)
Several types of cancer in fish are caused by retroviruses, including those responsible for major outbreaks of disease, such as walleye dermal sarcoma virus and salmon swim bladder sarcoma virus. These viruses form a phylogenetic group often described as the epsilonretrovirus genus. Epsilon-like retroviruses have become endogenous retroviruses (ERVs) on several occasions, integrating into germ line cells to become part of the host genome, and sections of fish and amphibian genomes are derived from epsilon-like retroviruses. However, epsilon-like ERVs have been identified in very few mammals. We have developed a pipeline to screen full genomes for ERVs, and using this pipeline, we have located over 800 endogenous epsilon-like ERV fragments in primate genomes. Genomes from 32 species of mammals and birds were screened, and epsilon-like ERV fragments were found in all primate and tree shrew genomes but no others. These viruses appear to have entered the genome of a common ancestor of Old and New World monkeys between 42 million and 65 million years ago. Based on these results, there is an ancient evolutionary relationship between epsilon-like retroviruses and primates. Clearly, these viruses had the potential to infect the ancestors of primates and were at some point a common pathogen in these hosts. Therefore, this result raises questions about the potential of epsilonretroviruses to infect humans and other primates and about the evolutionary history of these retroviruses. IMPORTANCE: Epsilonretroviruses are a group of retroviruses that cause several important diseases in fish. Retroviruses have the ability to become a permanent part of the DNA of their host by entering the germ line as endogenous retroviruses (ERVs), where they lose their infectivity over time but can be recognized as retroviruses for millions of years. Very few mammals are known to have epsilon-like ERVs; however, we have identified over 800 fragments of endogenous epsilon-like ERVs in the genomes of all major groups of primates, including humans. These viruses seem to have circulated and infected primate ancestors 42 to 65 million years ago. We are now interested in how these viruses have evolved and whether they have the potential to infect modern humans or other primates.